Ancient Epic : literary and linguistic essays - Díaz de Cerio Díez, Mercedes; Cabrillana, Concepción; Criado, Cecilia (Cambridge Scholars Publishing, 2015)
This book adopts a broad and multifaceted approach to that most preeminent of classical literature genres: the Epic. Set in the ancient world, from archaic Greece to imperial Rome, the scope of interest here extends, for comparative purposes, to Vedic and Sanskrit poetry, as well as the Medieval epic. This collection of papers by classicists from the University of Santiago de Compostela, Spain, embraces key themes in recent scholarship, such as the character of the hero, defined in terms of the conflict of power central to the epos, the metapoetic function of the bard as a literary reflection.